Cost-effectiveness of targeted screening for active pulmonary tuberculosis among asylum-seekers. (30th September 2020) - Wahedi, K; Biddle, L; Bozorgmehr, K
Abstract: Background: Screening asylum-seekers for active pulmonary tuberculosis is common practice among many European countries with low incidence of tuberculosis. The reported yields vary substantially, partly due to the heterogeneous and dynamic nature of asylum-seeking populations. Some countries apply targeted screening measures based on the incidence of tuberculosis in the country of origin. Evaluations of such approaches with respect to (cost)-effectiveness is scarce. Methods: Using screening data from a large German state over 14 years (2002-2015), we evaluate the cost-effectiveness of targeted screening based on WHO-reported incidence of tuberculosis in country of origins (from thresholds of 50 to 250/100, 000 inhabitants). Incremental cost-effectiveness is measured as cost per case found and cost per case prevented. Results: Incremental cost-effectiveness ratios (ICERs) of screening asylum-seekers from countries with an incidence of 50 to 250/100, 000 range between 15, 000€ and 17, 000€ per additional case found when compared to lower thresholds. The ICER for additional screening of asylum-seekers from countries with an incidence <50/100, 000 is 112, 000€ per additional case found. Costs per case prevented show a similar increase in costs. Conclusions: The high cost per case found or case prevented in the <50/100, 000 threshold scenario suggests this threshold to be a sensible cut-off for targeted screening. Acknowledging that no screening measure can find all cases of tuberculosis, and that reactivation of latent infections makes up a large proportion of foreign-born cases, targeting asylum-seekers from countries with an incidence above 50/100, 000 is likely to be a more reasonable screening measure for the prevention and control of tuberculosis than indiscriminate screening measures. Key messages: We challenge the widespread belief that indiscriminate tuberculosis screening programmes are placed at an acceptable balance between costs and benefits. Targeting asylum-seekers from countries with an incidence above 50/100, 000 is likely to be a reasonable screening measure for the prevention and control of tuberculosis.